Credit or Financing Analysis in Banking Institutions in the Perspective of Qiyas - Kusnoto; Athoillah, Mohamad Anton; Sholehudin, Ending; Huda, Uu Nurul; Bambang Waluyo (Nurani, 2024)
Banks, including Islamic banks, prioritize caution when lending money by using credit analysis methods like the 5C and 7P frameworks. Before approving a loan or financing request, banks assess applicants to minimize the chance of defaults. Questions arise regarding the law of credit analysis in banks from the perspective of the Qur’an, which is the source of Islamic economic law. This research is qualitative research with a normative juridical approach by examining legal verses in the Qur’an and linking them to qiyas. The research results show that verse 5 and 6 of the an-Nisa contain a prohibition on handing over assets to people who are not competent to manage them and contain orders to carry out tests before handing over a funds. 'The law contained in the condition is that in the case of incompetence in managing funds, testing is required before handing over the funds. Overall, the study concludes that credit analysis practices in banks align well with these principles, making them not only advisable but also encouraged under Islamic law.